Healthy ageing in Malaysia by 2030: needs, challenges and future directions - Abdullah, Jafri Malin; Ismail, Amin; Yusoff, Muhamad Saiful Bahri (Penerbit Universiti Sains Malaysia, 2024)
This Editorial addresses the critical need for developing a healthy ageing society in Malaysia by 2030. With the country’s elderly population projected to increase significantly, the article explores current challenges, including healthcare disparities, a shortage of geriatric specialists and malnutrition. It evaluates existing policies and highlights successful international and local initiatives, suggesting specific recommendations to improve healthcare infrastructure, healthy ageing support and technological integration. Emphasising the importance of engaging private sectors, non-governmental organisations (NGOs) and community groups, this Editorial calls for a collaborative approach to address the economic and cultural aspects of ageing. This comprehensive strategy aims to ensure a resilient, healthy and inclusive environment for Malaysia’s ageing population by 2030.